Team swimming in ant spermatozoa - Pearcy, Morgan (The Royal Society, 2014)
In species where females mate promiscuously, competition between ejaculates from different males to fertilize the ova is an important selective force shaping many aspects of male reproductive traits, such as sperm number, sperm length and sperm–sperm interactions. In eusocial Hymenoptera (bees, wasps and ants), males die shortly after mating and their reproductive success is ultimately limited by the amount of sperm stored in the queen's spermatheca. Multiple mating by queens is expected to impose intense selective pressure on males to optimize the transfer of sperm to the storage organ. Here, we report a remarkable case of cooperation between spermatozoa in the desert ant Cataglyphis savignyi. Males ejaculate bundles of 50–100 spermatozoa. Sperm bundles swim on average 51% faster than solitary sperm cells. Team swimming is expected to increase the amount of sperm stored in the queen spermatheca and, ultimately, enhance male posthumous fitness.